Custo de produção e indicadores de rentabilidade da cultura do milho safrinha - Furlaneto, Fernanda de Paiva Badiz; Esperancini, Maura Seiko Tsutsui [UNESP] (FapUNIFESP (SciELO), 2010)
The objective of this study was to evaluate the production cost and profitability of the second season corn crop in the Medio Paranapanema region, São Paulo State Brazil, under two technological levels (middle and high technology), crop 2008/2009, and compare the results with the 2006/2007 agricultural year. Effective and total operational cost as well as five profitability indicators were used. It was concluded that the high technology production cost for corn crop (direct seedling, sowing during the recommended period, use of simple hybrid seed, application of side-dressing fertilization, and treatment of seeds with different insecticides) was superior to the middle technology production cost (direct seedling, sowing after the recommended time, use of double hybrid seed, and no side-dressing fertilization). However, the average cost was inferior (US$ 8.5), due to a higher yield (4 t). The high technology corn crop was profitable (gross income and profitability index of 14% and 12%, respectively). For the middle technology crop, profitability indexes pointed out that the cropping system needs to be reevaluated by technicians and research institutions, regarding the adequate technical recommendations. Profitability indexes decreased considerably in both cropping systems. It was verified that, in relation to the 2006/2007 harvest period, the total operational cost increased for both technologies, mainly because of the increase of supplies prices.
Production cost and profitability of second season corn crop
Keywords: Economic return; Profitability; Second corn crop; Technological level; Zea mays